2015
DOI: 10.1016/j.jpag.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Nutrition, Physical Activity, and Birth Outcomes in Adolescent Girls

Abstract: Background Recommendations for preconception care usually include optimal nutrition and physical activity, but these have not been tested extensively for their relationship with birth outcomes such as low birthweight and preterm birth. Methods Data from Waves I, II and IV of the National Longitudinal Study of Adolescent Health (Add Health) contractual dataset were utilized. In Wave I in-home interview, participants were asked to recall their frequency of having five types of food on the previous day, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…Only 2.4% of the youth reported eating these vegetables every day and 19.5% of the youth never ate them. Xie, et al have also reported low levels of fruit and vegetable intake among pregnant youth in the USA [26].…”
Section: Discussionmentioning
confidence: 98%
“…Only 2.4% of the youth reported eating these vegetables every day and 19.5% of the youth never ate them. Xie, et al have also reported low levels of fruit and vegetable intake among pregnant youth in the USA [26].…”
Section: Discussionmentioning
confidence: 98%
“…Direct comparisons of our results with other studies are difficult as there are no precedents. Previous longitudinal cohort studies differed in target population and timing of the exposure and only studied birth weight, birth length, and preterm delivery 25,26 . In a US-based study of adolescent mothers (n = 833), where measures of diet and offspring neonatal outcomes were much closer together in time, no associations were identified between self-reported diet and birth weight and preterm delivery of offspring 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous longitudinal cohort studies differed in target population and timing of the exposure and only studied birth weight, birth length, and preterm delivery 25,26 . In a US-based study of adolescent mothers (n = 833), where measures of diet and offspring neonatal outcomes were much closer together in time, no associations were identified between self-reported diet and birth weight and preterm delivery of offspring 25 . In an Australian cohort of women, lower diet quality 10-15 months before pregnancy (low vegetable and whole-grain intakes) was associated with lower birth weight but not with preterm delivery 27 .…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines recommended that healthy adult pregnant women follow the same guidelines as healthy adults: at least 2.5 hours (150 minutes) per week of moderate aerobic activity, or approximately 21 minutes of brisk walking (or similar activity) each day. 2 PA patterns of pregnant women age 16 and older in the United States have been characterized by Evenson and Wen using National Health and Nutrition Examination Survey (NHANES) data (n 5 1280). 3 These data showed that most adult pregnant women in this survey failed to meet national PA guidelines.…”
Section: Introductionmentioning
confidence: 99%